PERANCANGAN ANIMASI 3D MASKOT SEBAGAI MEDIA UNTUK MENINGKATKAN BRAND AWARENESS PADA BENGKEL MOBIL PANDAWA AUTOWORKS : DESIGN OF A 3D MASCOT ANIMATION AS A MEDIA TO INCREASE BRAND AWARENESS AT PANDAWA AUTOWORKS CAR WORKSHOP - Mochamad Zidan Nur kamal; Aulia Hamdi; Muhammad Syaiful Amin (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
The automotive workshop industry in Indonesia has experienced significant growth along with the increasing number of motor vehicles. This condition has intensified competition among workshops, making effective visual communication strategies essential for improving brand awareness. Pandawa Autoworks has shown promising digital performance; however, it does not yet have a mascot that consistently represents its brand identity in promotional media. This study aims to design and develop a 3D animated mascot as a visual communication medium to enhance the brand awareness of Pandawa Autoworks. The research employed the ADDIE method, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The development process was carried out using Blender software through modeling, coloring, rigging, animation, and rendering stages. The resulting mascot animation was implemented in one of Pandawa Autoworks’ Instagram promotional contents. Evaluation was conducted using the Alpha Testing method involving Afif Nur Zaky, the owner of Pandawa Autoworks, and Khoerul Anam as an animation expert. The evaluation results showed an average score of 88.40 from the workshop representative and 87.30 from the animation expert, with an overall average score of 87.85, categorized as Very Good. The findings indicate that the developed 3D animated mascot is feasible as a visual communication medium and can support efforts to improve Pandawa Autoworks’ brand awareness on social media..